Intelligence Failures in the Asymmetric War between Ukraine and Russia: A Literature Review of Ukraine's Drone Attacks on Russian Military Infrastructure - Ito, Tarsito (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The asymmetric war between Ukraine and Russia since the Russian invasion in February 2022 has demonstrated a major transformation in the conduct of modern warfare. This study focuses on analyzing Russia’s intelligence failures in responding to Ukraine’s drone attacks on Russian military infrastructure. Despite its limited conventional military resources, Ukraine has successfully employed tactical strategies by utilizing low-cost yet effective drone technology, including First-Person View (FPV) and modified commercial drones. These attacks have damaged Russia’s strategic targets and exposed structural vulnerabilities in Russia’s defense and intelligence systems. This research explores how Russia’s intelligence system, which relies on hierarchical and conventional approaches, has failed to adequately prepare for new threats posed by lightweight, flexible technologies. Using a qualitative literature review method, this study identifies that shifting toward low-tech warfare and systemic disruption requires profound reforms in Russia’s intelligence structure and defense system. These findings are relevant in the military context and provide important insights for resource-constrained countries in designing more adaptive defense strategies against asymmetric threats in the 21st century.